Assessment and management of the risk of SARS-CoV-2 infection in an IVF laboratory. Issue 3 (September 2020) - Maggiulli, Roberta; Giancani, Adriano; Fabozzi, Gemma; Dovere, Lisa; Tacconi, Luisa; Amendola, Maria Giulia; Cimadomo, Danilo; Ubaldi, Filippo Maria; Rienzi, Laura
Abstract: Research question: The study set out to identify corrective measures aimed at reducing the risk of aerosol-mediated viral infection within an IVF laboratory. Design: A failure modes and effect analysis (FMEA) was conducted by a multidisciplinary IVF team. A schematic representation of new protocols and procedures adopted during COVID-19 emergency has been defined, including directives about the behaviour to adopt when entering the clinic and the laboratory, in case of face-to-face contact with patients and between staff members. In addition, the risk of cross-contamination between samples belonging to different patients during cell handling and manipulation has been evaluated. Potential failure modes for each phase of the emergency have been analysed, focusing on possible sources of error. Risk priority numbers have been calculated as products of Occurrence × Severity × Detection scores. Results: Except for cell–cell contamination, which was considered highly unlikely, failure modes during patient–staff, staff–staff and staff–cell interactions were estimated as carrrying a moderate to high risk of infection. The main corrective measures entailed precautionary logistic measures, the implementation of additional personal protective equipment and changes in the IVF laboratory procedures and scheduling of the daily routine. Some procedures were also revised, aiming to increase staff's awareness and caution. Conclusions: Standard laboratory protocols are insufficient to face a virus whose transmission is aerosol mediated. The measures outlined in this FMEA should thus be considered not only for facing this pandemic, but also for the future to promptly manage any aerosol-mediated virus infection, whose impact on the management of an IVF laboratory might be less severe than COVID-19 although not completely negligible.